NFIA haploinsufficiency: case series and literature review - Dini, Gianluca; Verrotti, Alberto; Gorello, Paolo; Soliani, Luca; Cordelli, Duccio Maria; Antona, Vincenzo; Mencarelli, Amedea; Colavito, Davide; Prontera, Paolo (Frontiers in Pediatrics, 2023)
Background NFIA-related disorder (OMIM #613735) is an autosomal dominant neurodevelopmental disorder characterized by a variable degree of cognitive impairment and non-specific dysmorphic features. To date, fewer than thirty patients affected by this disorder have been described. Methods Our study included three children with NFIA haploinsufficiency recruited from three medical genetics centers. Clinical presentations were recorded on a standardized case report form. Results All patients presented a variable degree of intellectual disability. None of the individuals in our cohort had urinary tract malformations. Three novel mutations, c.344G>A, c.261T>G, and c.887_888del are reported here. Conclusion NFIA haploinsufficiency can be suspected through careful observation of specific dysmorphisms, including macrocephaly and craniofacial abnormalities. Instrumental tests such as MRI and renal ultrasound provide further diagnostic clues, while genetic testing can confirm the diagnosis.